Novel Approach for Predicting Performance Degradation in Cloud (International Journal of Engineering and Computer Science, 2014)
Cloud computing is became an important paradigm in IT sector. Features like on demand service, cost effectiveness, elasticity made it possible. Because of these features and no upfront investment, many organizations using Cloud for their computational needs. But some organizations still worry about quality of service. To address this issue SLA is generated between Cloud provider and client organization. Avoiding SLA violation becomes necessary for cloud provider which leads in necessity of predicting performance degradation so that necessary action to avoid violation could be carried out. In this work we addressed above issue. Our work focuses on CPU cycles as resource to predict performance degradation of Cloud. Our result shows that performance of Cloud degrades when CPU usage of Virtual Machine (VM) running on cloud increases. We proposed system to predict performance degradation in Cloud.